Highly sensitive detection of E2 activity in ubiquitination using an artificial RING finger. (17th January 2017) - Miyamoto, Kazuhide; Sumida, Miho; Yuasa‐Sunagawa, Mayumi; Saito, Kazuki
Abstract : The ubiquitin‐conjugating (E2) enzymes of protein ubiquitination are associated with various diseases such as leukemia, lung cancer, and breast cancer. Rapid and accurate detection of E2 enzymatic activities remains poor. Here, we described the detection of E2 activity on a signal accumulation ISFET biosensor (AMIS sensor) using an artificial RING finger (ARF). The use of ARF enables the simplified detection of E2 activity without a substrate. The high‐sensitivity quantitative detection of E2 activities was demonstrated via real‐time monitoring over a response range of femtomolar to micromolar concentrations. Furthermore, the monitoring of E2 activities was successfully achieved using human acute promyelocytic leukemia cells following treatment with the anticancer drug bortezomib, which allowed the assessment of the pathological conditions. This strategy is extremely simple and convenient, and the present detection could be widely applied to specific E2s for various types of cancers. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : We performed the real‐time detection of E2 activities using ARF on a Micro Bioactive Analyzer (AMIS‐101) equipped with an AMIS sensor. Addition of ARF in the AMIS sensor prompted the Ubiquitin (Ub) transfer from the E2 conjugates, which led to the accumulation of Ub‐ARF conjugates. The proton changes in the ARF reaction were observed as the altering of the electron polarization in the sensing layer of the AMIS sensor, and thus, E2 activity was detected as the AMIS signal.